New chances for modern earth building - Steingass, Peter (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2003)
Earth has been a tried and tested natural building material for thousands of years, and in combination with modern techniques can be used for modern ecological buildings. This paper will describe the development of earth building in Germany and discuss finally the new chances of modern earth building. Additionally, the paper will briefly review the evolution of earth building in Germany, it will describe the technical development of earth building products and the next steps for a future dissemination.